Study of some bidentate schiff bases of isatin as corrosion inhibitors for mild steel in hydrochloric acid solution - Singh A.K.; Quraishi M.A. (My University, 2025)
The effect of Schiff base compounds, namely, ethylenediamine bis-isatin (EDBI), hexane 1,4-diamine bis-isatin (HDBI) and thiocarbohydrazide bis-isatin (TCBI) were investigated by gravimetric, potentiodynamic polarization, electrochemical impedance spectroscopy, atomic force microscopy and scanning electron microscopy. Although effect of molecular planarity on inhibition efficiency is observed from the results obtained between EDBI and HDBI. Adsorption of these inhibitors obeyed the Frumkin adsorption isotherm. It was found that efficiency order followed by inhibitor is TCBI>EDBI>HDBI. This fact strongly suggests that, an efficient corrosion inhibitor molecule should be large one, planar, having unoccupied d-orbital and also containing an extensive number of π-electrons. © 2012 by ESG.